2007
DOI: 10.1002/chem.200700920
|View full text |Cite
|
Sign up to set email alerts
|

TiIV‐Catalyzed Asymmetric Sulfenylation of 1,3‐Dicarbonyl Compounds

Abstract: The electrophilic enantioselective sulfenylation of 1,3-dicarbonyl compounds with phenylsulfenyl chloride is effectively catalyzed by [Ti(TADDOLato)] complexes. The corresponding products are obtained in moderate to high yields. The highest ee values (up to 97 %) are obtained in toluene at room temperature and with a typical catalyst loading of 5 mol %. Bulky ester groups and sterically undemanding substituents at the alpha-position were found to be crucial structural features of the starting materials in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 120 publications
(63 reference statements)
0
9
0
2
Order By: Relevance
“…A selectivity of up to 91:9 was obtained in D 2 O. A beneficial effect of the perfluoroarene–arene interactions on the enantioselectivity of a Ti(TADDOLato)‐catalyzed sulfenylation of β‐ketoesters with PhSeCl was found by Jereb and Togni 128. The reaction of a perfluoroarene substrate took place with 72 % ee , which is in slight contrast to the 62 % ee obtained with nonfluorinated arenes.…”
Section: Perfluoroarene–arene Interactionsmentioning
confidence: 95%
“…A selectivity of up to 91:9 was obtained in D 2 O. A beneficial effect of the perfluoroarene–arene interactions on the enantioselectivity of a Ti(TADDOLato)‐catalyzed sulfenylation of β‐ketoesters with PhSeCl was found by Jereb and Togni 128. The reaction of a perfluoroarene substrate took place with 72 % ee , which is in slight contrast to the 62 % ee obtained with nonfluorinated arenes.…”
Section: Perfluoroarene–arene Interactionsmentioning
confidence: 95%
“…[124] [128] Die Reaktion eines Perfluoraren-Substrats erfolgte mit 72 % ee im Unterschied zu 62 % ee für ein nichtfluoriertes Aren. Eine asymmetrische Photocyclisierung eines achiralen Diarylethens wurde in fester Phase über Perfluoraren-ArenWechselwirkungen erreicht.…”
Section: Aufsätzeunclassified
“…Ein günstiger Effekt von Perfluoraren-Aren-Wechselwirkungen auf die Enantioselektivität einer Ti(TADDOLato)-katalysierten Sulfonylierung von b-Ketoestern mit PhSeCl wurde von Jereb und Togni gefunden. [128] Die Reaktion eines Perfluoraren-Substrats erfolgte mit 72 % ee im Unterschied zu 62 % ee für ein nichtfluoriertes Aren. Eine asymmetrische Photocyclisierung eines achiralen Diarylethens wurde in fester Phase über Perfluoraren-Aren-Wechselwirkungen erreicht.…”
Section: Reaktionssteuerung Und Katalyseunclassified
“…However, mono derivatives are successfully prepared, and this is a limitation of other methods. [29] …”
Section: Resultsmentioning
confidence: 97%
“…[27] The asymmetric sulfenylation of -keto esters [28] would be expected to provide versatile building templates and synthons for biologically active molecules, [29] which is also in the purview of mono-sulfenylation. Tan et al reported carbon-tetrabromidemediated sulfenylation of active methylenes, via sulfenyl bromides as intermediates.…”
Section: Introductionmentioning
confidence: 99%